APLIKASI GANTT CHART PADA ALGORITMA PENJADUALAN PROSES - Sri Handayani; April Firman Daru (Jurnal Transformatika, 2014)
Operating system is a compulsory subject taken in the Information Technology Student FTIK - USM . In the discussion of the material management process of the operating systems course , there are some scheduling algorithm which processes need to be understood and any existing process scheduling algorithm presented in the form of Grantt Charts . Because of the difficulties experienced by students in understanding the process of scheduling algorithms by an Operating System become researchers inspiration to conduct this study to make an application Grantt Chart.. This study uses a waterfall system development , where the flow will follow the research the phase in waterfall . This application will be built using Visual Basic 6 .  The purpose of this research is to produce an application of learning are presented in graphical form to facilitate students in understanding the material scheduling process performed by an operating system so that students can also understand how a computer can do multiple processes simultaneously.